Home Alone - Zorn, Michelle L.; Shropshire, Christine; Martin, John A.; Combs, James G.; Ketchen, David J. (Strategic Management Journal, 2017)
[Research summary: Corporate scandals of the previous decade have heightened attention on board independence. Indeed, boards at many large firms are now so independent that the CEO is “home alone” as the lone inside member. We build upon “pro-insider” research within agency theory to explain how the growing trend toward lone-insider boards affects key outcomes and how external governance forces constrain their impact. We find evidence among S&P 1500 firms that having a lone-insider board is associated with (a) excess CEO pay and a larger CEO-top management team pay gap, (b) increased likelihood of financial misconduct, and (c) decreased firm performance, but that stock analysts and institutional investors reduce these negative effects. The findings raise important questions about the efficacy of leaving the CEO “home alone.” Managerial summary:Following concerns that insider-dominated boards failed to protect shareholders, there has been a push for greater board independence. This push has been so successful that the CEO is now the only insider on the boards of more than half of S&P 1500 firms. We examine whether lone-insider boards do in fact offer strong governance or whether they enable CEOs to benefit personally. We find that lone-insider boards pay CEOs excessively, pay CEOs a disproportionately large amount relative to other top managers, have more instances of financial misconduct, and have lower performance than boards with more than one insider. Thus, it appears that lone-insider boards do not function as intended and firms should reconsider whether the push towards lone-insider boards is actually in shareholders’ best interests.]